Deviation in Public Policy Implementation: An Analytical Study of QRIS in Indonesia - Nabila Nabila; Salsabilla Amalia Putri (Austronesia Akademika, 2025)
The transformation of digital payment systems has become a central focus of Indonesia’s financial inclusion agenda. One of the strategic policies in this context is the implementation of QRIS (Quick Response Code Indonesian Standard), launched by Bank Indonesia in 2019. This study aims to analyze the implementation of the QRIS policy in Indonesia from 2019 to 2025, using the theoretical and analytical framework of Mazmanian & Sabatier’s Policy Implementation Theory and Model. The research employs a descriptive qualitative approach, collecting data through literature review, policy document analysis, and secondary data from Bank Indonesia. The analysis focuses on six key variables derived from the theory: policy clarity, available resources, characteristics of implementing agencies, external environmental support, target group responses, and socio-economic conditions. The findings reveal that although the QRIS policy objectives are clearly defined and supported by adequate technological infrastructure, its implementation still faces challenges in digital literacy, adoption disparities across regions, and limited outreach to the informal sector. The coordination between implementing institutions also varies in effectiveness. In conclusion, while the national implementation of QRIS shows significant progress, its overall effectiveness depends heavily on strengthening human resources, improving policy communication strategies, and adapting to local socio-economic contexts. These findings contribute to the evaluation of technology-based public policy and offer a foundation for enhancing the effectiveness of future digital financial policies.